A Randomized Controlled Trial of Family Finding: A Relative Search and Engagement Intervention for Youth Lingering in Foster Care. (December 2017) - Vandivere, Sharon; Malm, Karin E.; Allen, Tiffany J.; Williams, Sarah Catherine; McKlindon, Amy
Background: Youth who have experienced foster care are at risk of negative outcomes in adulthood. The family finding model aims to promote more positive outcomes by finding and engaging relatives of children in foster care in order to provide options for legal and emotional permanency. Objectives: The present study tested whether family finding, as implemented in North Carolina from 2008 through 2011, improved child welfare outcomes for youth at risk of emancipating foster care without permanency. Research Design: A randomized controlled trial evaluation was carried out in nine counties in North Carolina. All children eligible for intervention services between 2008 and 2011 underwent random assignment. Effects were tested with an intent-to-treat design. Outcome data were obtained for all subjects from child welfare administrative data. Additional outcome data for a subset of older youth came from in-person interviews. Subjects: Subjects included 568 children who were in foster care, were 10–17 years old (at time of referral), had no identified permanent placement resource, and had no plan for reunification. Measures: The confirmatory outcome was moves to more family-like placements, whether through a step-down in foster care placement or discharge from foster care to legal permanency. Results: No impact on the confirmatory outcome was observed. Findings regarding exploratory impacts are also described; these must be interpreted with caution, given the large number of outcomes compared. Conclusions: The evaluation failed to find evidence that family finding improves the outcomes of older youth at risk of emancipation from foster care.